Behavioural shifts in toddlers: the consequences of early mobile phone usage - Ilango, Malar; Kumar, Mohan Prem (Indian Journal of Community Health, 2024)
I am writing to raise awareness about an issue in early childhood development: the impact of mobile phone usage on behaviour and development in children under five years old. With mobile devices becoming ubiquitous in our lives, understanding their influence on very young children is crucial for promoting healthy development and behaviour.